Odpowiedzi

Najlepsza Odpowiedź!
2010-01-20T16:13:34+01:00
A) x+2y - (x-5)(y+2)=
x+2y-(xy+2x-5y-10)=
x+2y-xy-2x+5y+10=
-x-xy+7y+10

b)-2(x-y)+ 8(4x-1)(1-y)=
-2x+2y+8(4x-4xy-1+y)=
-2x+2y+32x-32xy-8+8y=
-8+10y+30x-32xy

c)0,25(x+8y)-(0,5x +15)(1+0,5y)=
0,25x+2y-(0,5x+0,25xy+15+7,5y)=
0,25x+2y-0,5x-0,25xy-15-7,5y=
-0,25x-5,5y-15-0,25xy
2010-01-20T16:18:27+01:00
A)x+2y-(x-5)(y+2)=x+2y-xy-2x+5y+10=-x+7y-xy+10
b)-2(x-y)+ 8(4x-1)(1-y)=-2x+2y+32x-32xy-8+8y=30x+10y-32xy-8
c)0,25(x+8y)-(0,5x +15)(1+0,5y)=x/4+2y-0,5x-0,25xy-15-7,5y=
=-x/4-5,5y-0,25xy-15
1 5 1